The Four-Item Patient Health Questionnaire for Anxiety and Depression: A Validation Study in Infertile Patients - Azadeh Ghaheri; Reza Omani-Samani; Mahdi Sepidarkish; Mostafa Hosseini; Saman Maroufizadeh (International Journal of Fertility and Sterility, 2020)
Background: The most common mental disorders in infertile patients are depression and anxiety. The four-itemPatient Health Questionnaire-4 (PHQ-4) is a widely used tool that consists of the PHQ-2 depression and GeneralizedAnxiety Disorder-2 (GAD-2) scales. Given that PHQ-4 has not been validated in infertile patients, this study aimed toexamine its reliability and validity in this population.Materials and Methods: Participants in this cross-sectional study consisted of 539 infertile patients from a referralfertility centre in Tehran, Iran. The PHQ-4, Hospital Anxiety and Depression Scale (HADS), World Health Organisation-Five Well-Being Index (WHO-5), Penn State Worry Questionnaire (PSWQ) and demographic/infertility questionnaireswere administered to all participants. Factor structure and internal consistency of PHQ-4 were evaluatedvia confirmatory factor analysis (CFA) and Cronbach’s alpha, respectively. The convergent validity of this scale wasexamined by its relationship with HADS, WHO-5 and PSWQ.Results: CFA results provided support for a two-factor model of PHQ-4. Internal consistency of the PHQ-4 and its subscalesboth were elevated with Cronbach’s alpha coefficients of 0.767 (PHQ-4), 0.780 (PHQ-2) and 0.814 (GAD-2). Inter-itemcorrelations were between 0.386 and 0.639, and corrected item-total correlations were between 0.576 and 0.687. PHQ-4,PHQ-2 and GAD-2 showed positive correlations with measures of HADS-anxiety, HADS-depression, and PSWQ and negativecorrelations with WHO-5, which confirmed convergent validity. Among demographic/fertility variables, we observedthat gender, infertility duration, and failure in previous treatment were correlated with PHQ-4 and its subscales scores.Conclusion: The PHQ-4 is a reliable and valid ultra-brief screening instrument for measuring both anxiety and depressivesymptoms in infertile patients.